Analisis Kesalahan Berbahasa Tataran Morfologi pada Berita Harian Surat Kabar Tribun Medan - Ray, Sukma Adelina; Kusyani, Diah; Afipha Sakina Anjani, Nur; Daniya Putri, Anisa (Universitas Islam Sumatera Utara, 2024)
The focus of the problem in this study is the analysis of language errors at the morphological level in the June 17, 2023 edition of the Tribun Medan newspaper. The purpose of this study is to describe the analysis of language errors in the field of morphology in the Tribun Medan newspaper. This research method is qualitative research using a descriptive type. The data collection technique used is to read repeatedly the Tribun Medan newspaper, code any errors in the field of morphology, and record language errors in the field of morphology. This research method is qualitative research using a descriptive type. Based on the results of the analysis carried out, it can be concluded that there are errors at the morphological level consisting of 10 data which include: errors in the use of words in the abbreviation of morph me-, word formation with confixes di -...-kan, word writing/placement of wrong letter writing.